The presence of tumor-infiltrating FOXP3+ lymphocytes correlates with intratumoral angiogenesis in endometrial cancer. - Giatromanolaki, A; Bates, G; Koukourakis, M; Sivridis, E; Gatter, K; Harris, A; Banham, A (2008)
OBJECTIVES: CD4(+)CD25(+) regulatory T-cells (Tregs), that express the transcription factor FOXP3, suppress effector T-cell populations and can enable tumour cells to evade the host immune response. In this study, we investigated the numbers of FOXP3(+) Tregs in the normal and malignat endometrium and examined potential links with tumor angiogenesis. METHODS: Paraffin-embedded tissues from 79 patients with stage I endometrial adenocarcinoma and 12 samples from normal endometrium were analyzed using immunohistochemistry for the detection of FOXP3(+) lymphocytes. The presence of FOXP3(+) lymphocytic infiltration was correlated with the tumor vascular density, the hypoxia inducible factors HIF-1alpha and HIF-2alpha, VEGF, estrogen and progesterone receptor expression. Survival analysis was also performed. RESULTS: In normal endometrium, FOXP3 was expressed by stroma infiltrating lymphocytes, with a mean number 8 (range 5-11) lymphocytes per x100 optical field. In tumors, 55/79 (69.6%) cases showed little FOXP3(+) lymphocytic infiltration (0-2 per x100 optical field). In the remaining 24/79 (30.4%) cases that were scored as positive the mean score ranged from 3-8 (median 5). Low numbers of FOXP3(+) lymphocytes significantly correlated with tumoral ER negativity and low vascular density. Survival analysis showed no significant impact of FOXP3 lymphocytic infiltration, although there was a trend towards worse prognosis. CONCLUSIONS: The correlation between the presence of FOXP3(+) Tregs and high vessel density in endometrial adenocarcinomas suggests a link between immunity, intratumoral angiogenesis and poor prognosis. However, further studies are required as significantly fewer Tregs were detected in the tumor microenvironment compared to normal endometrium.